First-Time Voting in the UK 1997 General Election - McCormack, Una (Operant Subjectivity, 1997)
It is often assumed that "young people" are a homogenous group, and that the current generation of young people are politically disengaged, or, at best, only interested in issue politics. The Q study reported here demonstrated that both of these assumptions are false. The sorts provided by first-time voters produced seven highly divergent factors, demonstrating a wide range of viewpoints on politics, the political process and voting itself.